Proteomics in Biomedicine and Pharmacology - Donev, Rossen (Advances in protein chemistry and structural biology, 2014)
Volume 95 of Advances in Protein Chemistry and Structural Biology focuses on advances in proteomic techniques and their application in biomedicine and pharmacology. This volume describes in detail the applications of these techniques in studying a number of diseases and specific protein modifications and profiles, including phosphoproteomics, glycoproteomics, and more. Published continuously since 1944, the Advances in Protein Chemistry and Structural Biology series is the essential resource for protein chemists. Each volume brings forth new information about protocols.